ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING PADA SAAT INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Rahma Indria Puspita; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
This study aims to examine the variables that influence underpricing when initial public offering at the Indonesia Stock Exchange 2010-2012 period. The variables examined include industry age, the percentage of offers, offers time period, financial leverage, and the growth of total assets.The research was carried out by multiple regression analysis, data collection tools used were observational studies and literature study with purposive sampling method. Sample of 50 companies from a population of 71 companies. The research concluded that first industry age not proven effect on the level of underpricing, second the percentage of offers not proven effect on the level of underpricing, third offers time period shown proven effect on the level of underpricing, fourth financial leverage not proven effect on the level of underpricing, and fifth the growth of total assets shown proven effect on the level of underpricing.